IMPLEMENTASI DAN PENGUJIAN PROTOTIPE TURBIN JENIS PROPELLER UNTUK PEMBANGKIT LISTRIK TENAGA MIKROHIDRO - Sudiro, Rafiandi Dyaa; Halim, Levin; Arthaya, Bagus Made (Jurnal Rekayasa Mesin, 2024)
The implementation of a small-scale Micro-Hydro Power Plant which considering a 2-meter water head river will be discussed in this research. Therefore, a Micro-Hydro Power Plant with a Propeller turbine type was implemented. The turbine components include the turbine wheel, blades, guide vanes, turbine housing, turbine cover, and discharge pipe. Each component was manufactured using a 3D printing process with PLA filament. The testing process involved a miniature dam made from a container with a height of 1 meter, connected vertically with pipes. Water flowing into the turbine rotates the turbine wheel, causing it to rotate on the turbine shaft. Output data, including rthe number of rotations (RPM) and torque (M), were collected using sensors placed on the turbine wheel shaft. The testing results of the prototype Propeller turbine showed an efficiency of over 90% at a flow rate of approximately 0.008 m^3/s. Under the ideal design conditions with 90% efficiency, the prototype turbine would operate at a rotation speed of 2880 RPM and generate a power output (P) of 66 Watts.